Single-stage reconstruction of rhinophyma: a case report - Chodankar, Sandesh; Rane, Pawan (International Journal of Research in Medical Sciences, 2025)
Rhinophyma, an advanced form of rosacea, is characterized by progressive nasal enlargement leading to significant cosmetic and functional impairments. This case report details the management of a 54-year-old male presenting with a 10-year history of nasal hypertrophy consistent with rhinophyma. The patient had surgery in steps that included using a flap from his forehead to rebuild the shape of his nose. Postoperative care included targeted antibiotic therapy and meticulous wound management. Over a nine-month follow-up period, the patient's recovery was satisfactory, with significant aesthetic and functional improvements. This case demonstrates the effectiveness of a systematic surgical strategy in treating advanced rhinophyma.